Impact of cyber safety and security literacy program on cyber etiquette of prospective teachers - Santhosh Thangan; Thiyagu Kaliappan; Vrinda Vijayan; Venukanti Sai Abhinav; Mandala Chandrashekhargoud; Suresh Anuganti (Journal of Education and Learning (EduLearn), 2026)
This research aims to evaluate the effectiveness of a module-based intervention program called cyber safety and security literacy program (CSLP) on cyber etiquette among prospective teachers. The entire study was divided into two major sections, namely: i) design and development of the CSLP; and ii) assessing the impact of the program. For the design, the research and development (RD) method was used. To assess the impact of the program a quasi-experimental design was followed. Pre-experimental research with a one group pre-test and post-test design was adopted to measure the impact. The convenience sampling method was adopted for the selection of the sample. 50 prospective teachers from various training colleges in India participated in the study. The cyber etiquette scale with 50 items (Cronbach’s α=0.889) and valid (Kaiser-Meyer-Olkin (KMO) value=0.804) used for this purpose. The study’s findings highlight the effectiveness of the intervention in promoting responsible digital behavior, evidenced by the substantial improvements in participants’ pre-test and post-test scores. The strong positive correlation (r=0.74) and large effect size (Cohen’s d=5.16) confirm the program’s success in fostering higher levels of cyber safety awareness and ethical online conduct.